Technology and identity: the case of the Inuit and Facebook - Castleton, Alexander (CIC. Cuadernos de Información y Comunicación, 2017)
This article discusses the relationship between technology, cultural identity, and social change in the Canadian Arctic. Using an ethnographic strategy based on interviews and digital content observation, I explore how a group of students from the Arctic College located in the community of Iqaluit located on Baffin Island in the Canadian Arctic, use the social networking site Facebook. I found that, in addition to an expected use of the social network associated with the script of the technology, Inuit youth use Facebook to access content related to their identity, discuss cultural issues, and recall traditions. This article argues that the Inuit identity is an example of how indigenous cultures have to be understood as something dynamic and in constant change for which ICTs are fundamental. Inuit identity includes artifacts such as computers, the Internet or Facebook for the affirmation and practice of their culture.
Keywords: Identity; ICT; Facebook; Inuit.